Perfil socioeconômico dos alunos atendidos pelo projeto UNATI da UNESP/Tupã - Regazzo, Carolina [UNESP] (2015)
The project Universidade Aberta à Terceira Idade aims to approximate the university and the elderly population. In the city of Tupã - SP, the project, offered by Univ Estadual Paulista – UNESP, capacities 60 students a year since 2010. This research aims at describing socioeconomical profile of students enrolled in this project.